2020
DOI: 10.1177/0954410020953046
|View full text |Cite
|
Sign up to set email alerts
|

Transonic flutter characteristics of an airfoil with morphing devices

Abstract: An investigation into transonic flutter characteristic of an airfoil conceived with the morphing leading and trailing edges has been carried out. Computational fluid dynamics (CFD) is used to calculate the unsteady aerodynamic force in transonic flow. An aerodynamic reduced order model (ROM) based on autoregressive model with exogenous input (ARX) is used in the numerical simulation. The flutter solution is determined by eigenvalue analysis at specific Mach number. The approach is validated by comparing the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although, the authors of this research acknowledge that this is an aspect to focus on in the future as aeroelastic phenomena such as flutter and buffet may result in negative effects for the structural integrity of the wing. As regarded in the investigation of He et al [45] in which the author found that this technology can be of use to control the flutter generated by manipulating the harmful eddies and enhancing the beneficial ones by means of a vibrating TE (locking effect). Tô et al [46] focused their research on the effects of flutter when morphing technology is used in the TE concluding that the implementation of a morphing part can increase the transonic flutter speed up to 74.5%, as the shock wave can change of location and formation due to the change in the deflection of the morphing region.…”
Section: Methodsmentioning
confidence: 99%
“…Although, the authors of this research acknowledge that this is an aspect to focus on in the future as aeroelastic phenomena such as flutter and buffet may result in negative effects for the structural integrity of the wing. As regarded in the investigation of He et al [45] in which the author found that this technology can be of use to control the flutter generated by manipulating the harmful eddies and enhancing the beneficial ones by means of a vibrating TE (locking effect). Tô et al [46] focused their research on the effects of flutter when morphing technology is used in the TE concluding that the implementation of a morphing part can increase the transonic flutter speed up to 74.5%, as the shock wave can change of location and formation due to the change in the deflection of the morphing region.…”
Section: Methodsmentioning
confidence: 99%